Bioactivity of Bacillus Species Isolated from Human Feces - Adnan, H. Abbas; Jabbar, F. Al-Maadhidi; Mahdi, S. Al-Rubaie (Journal of Madenat Alelem University College, 2012)
In the present study, twenty isolates of Bacillus genus according to morphological feature of colonies and the presence of spores by light microscopy, were obtained from 15 samples of human feces, after heat-treated and killed all vegetative cells. These spore-former isolates were characterized at the species level biochemically by the use of API 50 CHB kit and identified as Bacillus insolitus, B. laterosporus, B. polymyxa and B. bodius with proportion ratio rate 40, 20, 35 and 5% of the total, respectively. Eighty five percent of Bacillus isolates were formed biofilm, which have protective and adhesive properties and could be responsible for an increased antibiotics resistance. Seventy five percent of Bacillus species isolated from human feces were produced inducible extracellular Levansucrase and responsible for synthesis of fructan polymers (levan), described as useful prebiotics due to the capacity of the β-linked fructose units. Five Bacillus species were showed positive result for Exopolysaccharides production. Bacillus species resistant to Ampicillin (AP), Chloramphenicol (C), Nitrofurantoin (NI), Gentamicin (GM), Carbenicillin (PY), Nalidixic acid (NA), Methenamine Mandelate (MM), and Cotrimoxazole (TS), reached 20, 100, 60, 0.0, 5, 95, 5 and 70%, respectively.